2012
DOI: 10.1136/jmedgenet-2011-100195
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation in coagulationF7gene influences plasma FVII concentrations and relates to coronary artery disease

Abstract: Epigenetic regulation through methylation of F7 promoter is associated with CAD by affecting plasma FVIIa concentrations in A1A1 genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 37 publications
2
26
0
1
Order By: Relevance
“…F5 has been reported to be involved in embolization and coagulation. Friso et al (2012) found that promoter methylation in the coagulation F7 gene can influence the concentrations of plasma F5II and is associated with coronary artery diseases. PTSD may elicit hypercoagulability, suggesting possible psychobiological characteristics, through which atherosclerosis progression and clinical cardiovascular disorders are attributed to PTSD (von Känel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…F5 has been reported to be involved in embolization and coagulation. Friso et al (2012) found that promoter methylation in the coagulation F7 gene can influence the concentrations of plasma F5II and is associated with coronary artery diseases. PTSD may elicit hypercoagulability, suggesting possible psychobiological characteristics, through which atherosclerosis progression and clinical cardiovascular disorders are attributed to PTSD (von Känel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined these polymorphisms in patients with venous and arterial thrombosis, but the results are very variable and sometimes contradictory (Athanasiadis et al, 2010;Lopaciuk et al, 2010;Eroğlu et al, 2010Eroğlu et al, , 2011Previtali et al, 2011;Friso et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of molecular biology technology, scientists have found many gene polymorphisms closely related to coronary heart disease susceptibility, such as those of angiotensin converting enzyme (Cambien et al, 1992;Narne et al, 2012), apolipoprotein (Hsu et al, 2006;Jang et al, 2009;Huang et al, 2012), cell factor (Zhong et al, 2009;Fragoso et al, 2010;Jin et al, 2012;Srikanth Babu et al, 2012), coagulation system (Pegoraro, 2005;Friso et al, 2012), and endothelin (Popov et al, 2008).…”
Section: Discussionmentioning
confidence: 99%